Shape of chondrocytes within articular cartilage affects the solid but not the fluid microenvironment under unconfined compression. (1st January 2016) - Guo, Hongqiang; Torzilli, Peter A.
Graphical abstract: Abstract: Metabolic activity of the chondrocytes in articular cartilage is strongly related to their zone-specific shape and the composition and mechanical properties of their surrounding extracellular matrix (ECM). However the mechanisms by which cell shape influences the response of the ECM microenvironment to mechanical loading is yet to be elucidated. This relationship was studied using a biphasic multiscale finite element model of different shaped chondrocytes in the superficial and deep zones of the ECM during unconfined stress relaxation. For chondrocytes in the superficial zone, increasing the cell's initial aspect ratio (length/height) increased the deformation and solid stresses of the chondrocyte and pericellular matrix (PCM) during the loading phase; for chondrocytes in the deep zone the effect of the cell shape on the solid microenvironment was time and variable dependent. However, for superficial and deep zone chondrocytes the cell shape did not affect the fluid pressure and fluid shear stress. These results suggest that mechanotransduction of chondrocytes in articular cartilage may be regulated through the solid phase rather than the fluid phase, and that high stresses and deformations in the solid microenvironment in the superficial zone may be essential for the zone-specific biosynthetic activity of the chondrocyte. The biphasic multiscale computational analysis suggests that maintaining the cell shape is critical for regulating the microenvironment and metabolic activity of the chondrocyte in tissue engineering constructs. Statement of significance: We investigated the effect of chondrocyte shape on the cellular microenvironment using a biphasic multiscale finite element analysis. Our study showed that cell shapes affects the solid but not the fluid microenvironment of the chondrocyte, and that maintaining the cell shape is critical for regulating the microenvironment and metabolic activity of the chondrocyte in native cartilage and tissue engineering constructs. As far as we know, this is the first study on the mechanotransduction mechanisms by which cell shape influences the response of the microenvironment to mechanical loading. This study is important for understanding cell mechanobiology, not only for regulation of cell phenotype in tissue engineered constructs but, as important, for understanding changes in normal chondrocyte function after post-traumatic injury and in the initiation and progression of osteoarthritis.